The 2016 Kumamoto Mw = 7.0 Earthquake: A Significant Event in a Fault–Volcano System. Issue 11 (27th November 2017) - Yue, Han; Ross, Zachary E.; Liang, Cunren; Michel, Sylvain; Fattahi, Heresh; Fielding, Eric; Moore, Angelyn; Liu, Zhen; Jia, Bo
Abstract: The 2016 Kumamoto earthquake sequence occurred on the Futagawa–Hinagu fault zone near the Aso volcano on Kyushu island. The sequence was initiated with two major ( Mw  ≥ 6.0) foreshocks, and the mainshock ( Mw  = 7.0) occurred 25 h after the second major foreshock. We combine GPS, strong motion, synthetic aperture radar images, and surface offset data in a joint inversion to resolve the kinematic rupture process of the mainshock and coseismic displacement of the foreshocks. The joint inversion results reveal a unilateral rupture process for the mainshock involving sequential rupture of four major asperities. The slip area of the foreshocks and mainshock and the aftershock loci form a detailed complementary pattern. The mainshock rupture terminates near the rim of the caldera, leaving a ~10 km long gap of aftershocks. This area is characterized by high temperature and low shear wave velocity, density, and resistivity, which may be related to the partially melted geothermal condition. Ductile material property near the volcano may act as a "material barrier" to the dynamic rupture. Topographic weight of the caldera increases compressional normal stress on the fault plane, which may behave as a "stress barrier." Long‐term seismic hazard and deformation behaviors related to these two types of barriers are discussed in terms of the associated frictional mechanism. Significant postseismic creeps observed near the volcano area indicates a velocity strengthening frictional behavior near the rupture termination, which confirms that the "material barrier" mechanism is likely the dominant rupture termination mechanism. Key Points: Detailed slip model of Kumamoto earthquake sequence resolved Innovative model parameterization adopted in inversion Effects of "material" and "stress" barriers classified and discussed